Who's Driving Whom? : Analyzing External and Intra-Regional Linkages in the Americas - Zettelmeyer, Jeromin (Departmental Papers; Departmental Paper ;, 2008)
In a global economy beset by concerns over a growth recession, financial volatility, and rising inflation, countries in the Western Hemisphere have been among the few bright spots in recent years. This has not come as a surprise to those following the significant progress achieved by many countries in recent years, both in macroeconomic management and on the structural and institutional front. Hence, there can be little doubt, as this book argues, that economic and financial linkages between Latin America, the United States, and other important regions of the world economy have undergone profound change.